Fatigue Crack Growth of SLM Ti-4Al-6V Processed by Ultrasonic Impact Treatment; AIP Conference Proceedings; Vol. 2167 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2019 (AMHS'19) - Eremin A. V. Alexandr Vyacheslavovich; Burkov M. V. Mikhail Vladimirovich; Panin S. V. Sergey Viktorovich; Byakov A. V. Anton Viktorovich (2019, 2019)
Title screen